2022
DOI: 10.3390/microorganisms10112255
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Probiotics: A Novel Preventive Approach for the Control of Bovine Mastitis

Abstract: Bovine mastitis (BM) is one of the most common diseases of dairy cattle, causing economic and welfare problems in dairy farming worldwide. Because of the predominant bacterial etiology, the treatment of BM is mostly based on antibiotics. However, the antimicrobial resistance (AMR), treatment effectiveness, and the cost of mastitis at farm level are linked to limitations in the antibiotic therapy. These scenarios have prompted the quest for new preventive options, probiotics being one interesting alternative. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…It was demonstrated that oral treatment of L. casei Zhang and L. plantarum P-8 drastically decreased SCC and increased milk production. 173 The self-assembly tilmicosin nanogel by a combination of SLN technology with in-situ hydrogel technology improves the treatment effect of tilmicosin against S. aureus cow mastitis. 174 Herbal therapy can be used in the treatment of mastitis as it has no side effects.…”
Section: Treatmentmentioning
confidence: 99%
“…It was demonstrated that oral treatment of L. casei Zhang and L. plantarum P-8 drastically decreased SCC and increased milk production. 173 The self-assembly tilmicosin nanogel by a combination of SLN technology with in-situ hydrogel technology improves the treatment effect of tilmicosin against S. aureus cow mastitis. 174 Herbal therapy can be used in the treatment of mastitis as it has no side effects.…”
Section: Treatmentmentioning
confidence: 99%
“…Other alternatives have included the use of probiotics [ 163 , 164 ], zeolites [ 165 , 166 ], cytokines [ 167 , 168 , 169 , 170 ], ozone [ 171 , 172 , 173 ], and aloe vera [ 174 , 175 ]. Zeolites are natural, microporous, three-dimensional crystalline materials with well-defined channels and cavities and various technological applications in veterinary medicine [ 176 , 177 ].…”
Section: Alternative Strategies—potential Solutionsmentioning
confidence: 99%
“…Numerous studies have acknowledged the detrimental impact of mastitis on women's health and mammalian populations, prompting exploration into alternative treatments such as dietary fiber intake, geraniol, and probiotic interventions. [5][6][7][8] However, a comprehensive understanding of the risk factors, pathophysiology, and optimal treatment methods for mastitis remains incomplete; thus, it is necessary to employ multi-omics approaches to gain profound insights into the nature of this condition. 3,9 There is evidence indicating that disturbances in the intestinal microbiota play a significant role in the pathogenesis of inflammatory diseases, such as endometritis, cardiovascular diseases, and mastitis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, further elucidation of the pathogenesis of mastitis is imperative for accurate diagnosis and effective disease control. Numerous studies have acknowledged the detrimental impact of mastitis on women's health and mammalian populations, prompting exploration into alternative treatments such as dietary fiber intake, geraniol, and probiotic interventions 5–8 . However, a comprehensive understanding of the risk factors, pathophysiology, and optimal treatment methods for mastitis remains incomplete; thus, it is necessary to employ multi‐omics approaches to gain profound insights into the nature of this condition 3,9 …”
Section: Introductionmentioning
confidence: 99%